Contemporary practices of strength and conditioning coaches in professional cricket. Issue 3 (June 2021) - Weldon, Anthony; Duncan, Michael J; Turner, Anthony; Christie, Candice J; Pang, Cecilia MC
This study describes the contemporary practices of strength and conditioning (S&C) coaches in male professional cricket. Thirty-three S&C coaches working with international and professional club teams across seven countries completed an online survey. The survey consisted of 45 questions (35 fixed responses and 10 open-ended), with eight sections: (a) background information, (b) muscular strength and power development, (c) speed development, (d) plyometrics, (e) flexibility development, (f) physical testing, (g) technology use, and (h) programing. Most S&C coaches were educated to degree level (97%) or higher, with 91% of degrees being in a sports science-related field. Furthermore, 73% held S&C and 40% cricket coaching certifications. Isometric type resistance training exercises (94%) were frequently programed by S&C coaches, with squats and deadlifts (including variations) deemed the most important strength development exercises. Ratings of perceived exertion (58%) was most used for determining set loads. Hang clean (64%) and multiple hops/lunges (85%) were the most prescribed Olympic weightlifting and plyometric exercises. Speed gates (85%) were the most used technology-based equipment. Open-ended questions revealed, 45% of S&C coaches believed time constraints, scheduling and fixtures are the main issues faced in their role. Position-specific demands (61%) was the predominant method used for individualizing players training strategies. The information presented in this study is valuable for those pursuing or currently working as an S&C coach in professional cricket to align, compare, and explain their practices. Furthermore, will provide insight for the wider athlete support team (e.g., sports coaches and physiotherapists) on the practices of S&C coaches.